Taming galileons in curved spacetime. (10th November 2017) - Banerjee, Rabin; Mukherjee, Pradip
Abstract: Localising galileon symmetry along with Poincaré symmetry, we have found a version of the galileon model coupled with curved spacetime which retains the internal galileon symmetry in covariant form. Also, the model has second order equations of motion.